Pengaruh Brand Image dan Green Marketing terhadap Keputusan Pembelian AMDK Le Minerale di Kota Cirebon - Nur'aeni; Dewi Laily Purnamasari; Oryz Agnu Dian Wulandari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This study aims to analyze the influence of brand image and green marketing on purchasing decisions for bottled water, specifically among Le Minerale consumers in Cirebon City. This is a quantitative, associative study with a sample size of 100 respondents. The research method used a survey conducted via Google Forms in the form of questionnaire with a five-point Likert scale. The analysis tool used in this study was SmartPLS 4, employing several analyses, namely Validity Test, Discriminant Validity Test (HTMT, Fornell-Lacker Criteria, and Cross Loadings), Reliability Test, Model Fit Test, Determination Coefficient Test, Multicollinearity Test, Path Coefficient Test, and Simultaneous Test. The results of this study conclude that (1) brand image has a positive and significant influence on purchase decisions. (2) green marketing has a positive and significant influence on purchasing decisions. (3) brand image and green marketing simultaneously influence purchasing decisions. The influence of brand image and green marketing on purchasing decisions is 48%, while the remaining 52% is influenced by other variables.